2007
DOI: 10.1007/bf03262571
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a community-based dental registration program for preschool children living in areas of high social deprivation

Abstract: The adoption of a community-based approach assisted in promoting dental registration and access to dental services for preschool children residing in areas of high social deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(63 citation statements)
references
References 23 publications
0
63
0
Order By: Relevance
“…Similarly, when various measures of neighborhood advantage (i.e., neighborhood income, space, household values, etc.) are controlled, most (Gerst et al, 2011a; Halpern & Nazroo, 2000a; Lee, 2009a; Mair et al, 2010b; Neeleman et al, 2001; G V Ostir et al, 2003b; Yuan et al, 2007) but not all studies (Henderson et al, 2005; Mair et al, 2010a; Yuan et al, 2007) have found that the relationship of ethnic density to depression remained significant for at least one ethnic subgroup. Two studies (Mair et al, 2010b; Vogt Yuan, 2007) report that the negative relationship of ethnic density to depressive symptoms disappears when measures of neighborhood advantage are controlled, whereas in a majority of the studies the relationship persists (Das-Munshi et al, 2010a; Gerst et al, 2011a; Halpern & Nazroo, 2000a; Mair et al, 2010b; Mintz & Schuartz, 1964; G V Ostir et al, 2003b; Vogt Yuan, 2007; Walters et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, when various measures of neighborhood advantage (i.e., neighborhood income, space, household values, etc.) are controlled, most (Gerst et al, 2011a; Halpern & Nazroo, 2000a; Lee, 2009a; Mair et al, 2010b; Neeleman et al, 2001; G V Ostir et al, 2003b; Yuan et al, 2007) but not all studies (Henderson et al, 2005; Mair et al, 2010a; Yuan et al, 2007) have found that the relationship of ethnic density to depression remained significant for at least one ethnic subgroup. Two studies (Mair et al, 2010b; Vogt Yuan, 2007) report that the negative relationship of ethnic density to depressive symptoms disappears when measures of neighborhood advantage are controlled, whereas in a majority of the studies the relationship persists (Das-Munshi et al, 2010a; Gerst et al, 2011a; Halpern & Nazroo, 2000a; Mair et al, 2010b; Mintz & Schuartz, 1964; G V Ostir et al, 2003b; Vogt Yuan, 2007; Walters et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[2428, 32, 33, 35, 36, 39, 40] Four trials, however, were “quasi-experimental” with a pre-test/post-test design [20, 21, 34, and 37], two had equivalent [22, 29] and one had non-equivalent comparison group . [38] One included study was historically controlled non-randomized [23] and another was ecologic. [30] Table 1 …”
Section: Resultsmentioning
confidence: 99%
“…Seven home visiting programs [20, 23, 26&27, 36, 37, 38, 39] were reviewed as well whereas one intervention included both home visits and consultations at well-baby clinic. [22] Two studies [21, 38] reported including both urban and rural settings in their recruitment, five [23, 30, 34, 35, 37] were restricted to rural sites and three [25, 26, 28] to urbanized or metropolitan areas. Table 1 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations